Biosurfactants: Opportunities for the development of a sustainable future. (December 2021) - Manga, Enuh Blaise; Celik, Pınar Aytar; Cabuk, Ahmet; Banat, Ibrahim M.
Abstract: Changes in the environment in recent years have led to the examination of the role and influence human activities on it. Attempts to quantify the impact of these activities by developing standardized modeling frameworks through life cycle sustainability assessment is one such approach in the context of sustainability seeking to measure the impact of human interventions from a holistic perspective that includes economic, social, and environmental dimensions. Sustainable alternatives to synthetic products are always keenly sought after. Biosurfactants are emerging as suitable alternatives to the predominant less sustainable petroleum-derived counterparts. Several factors surrounding their production, distribution, and end-use, however, still needs to be considered before conclusively confirming their sustainability. Though data are still limited in that subject matter, research showing their impact on some sustainability indicators is highlighted. This review discusses the potential of biosurfactants as sustainable products in the context of social, economic, and environmental aspects. Graphical abstract: Image 1 Highlights: Biosurfactants are emerging as suitable, more sustainable alternatives to chemical counterparts. They are less antagonistic to human biology with positive antimicrobial and health applications. Biosurfactants enhance remediation of water, soil and overall environmental health. Biosurfactants can contribute to improving the sustainability of several industrial processes. Production, applications and life cycle assessment advances will ensure their future sustainability.